MORAL MESSAGES IN THE FILM IPAR ADALAH MAUT: A CHARLES SANDERS PEIRCE SEMIOTIC ANALYSIS - Dinda Putri Rahmawati; Sungkowo Sungkowo; Januri Januri (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study examines the moral messages embedded in the Indonesian film Ipar Adalah Maut (2024) through the semiotic framework of Charles Sanders Peirce. Film, as a medium of mass communication, fulfills not merely an entertainment function but also serves as a vehicle for the transmission of moral and social values within contemporary society. Through Peirce's triadic model of representamen, object, and interpretant, visual and verbal signs throughout the film were systematically observed and analyzed. The findings reveal a rich constellation of moral messages articulated across three primary dimensions: individual morality, encompassing self-integrity and personal accountability; social morality, addressing fidelity, trust, and the ethics of familial interaction; and religious morality, grounding the narrative in Islamic prescriptions concerning marital sanctity and the prohibition of transgression. The film further dramatizes the destructive consequences of khalwat (unsupervised proximity between non-mahram individuals) and the erosion of marital covenant (mitsaqan ghalizha). Peirce's analytical framework proves efficacious in unveiling the layered denotative and connotative meanings constructed through the film's cinematic symbolism, ultimately positioning the work as a compelling medium of visual da'wah.